Consumer insight on Tea Post: Exploring motivating factors driving footfall in Ahmedabad city. - Mustakim Momin; Manoj Prajapati; Jignesh Vidani (Journal of Advanced Research in Economics and Business Management, 2026)
This research investigates the motivating factors influencing consumers’ visits to tea outlets in India, with a focus on the role of gender in shaping preferences and behavior. Tea consumption in India is no longer limited to mere refreshment; it has evolved into a lifestyle and social experience, particularly among urban youth. The study employs a primary survey of 153 respondents, analyzing demographic variables such as gender, age, occupation, and income alongside behavioral factors including relaxation, taste preference, pricing, variety, ambience, health considerations, availability of snacks, brand reputation, promotional offers, and modern café culture. Reliability analysis confirmed a high internal consistency of the measurement items (Cronbach’s Alpha = 0.954). Cross-tabulation and chi-square tests reveal significant gender-based differences in several motivational factors, including relaxation, taste preference, affordability, ambience, convenience, and variety of tea options. While some factors such as health benefits and preference for modern café culture did not show significant gender differences, others indicate nuanced patterns in consumer decision-making. The findings have both theoretical and practical implications, highlighting the importance of gender-sensitive marketing strategies, experiential outlet design, and targeted promotional activities to enhance consumer satisfaction and loyalty. This study contributes to the understanding of consumer behavior in the contemporary Indian tea industry, providing actionable insights for entrepreneurs, café managers, and marketers seeking to optimize their offerings in alignment with evolving preferences.